Effectiveness of liquid organic-nitrogen fertilizer in enhancing nutrients uptake and use efficiency in corn (Zea mays) - Kasim, Susilawati; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Academic Journals, 2011)
The ever increasing price of nitrogenous (N) fertilizers coupled with the deleterious effects of imbalanced N fertilizers on the environment necessitates the enhancement of N use efficiency of plants. The objectives of this study were to: (1) Evaluate the uptake of selected nutrients due to application of liquid organic-N fertilizers and (2) determine the efficiency of the formulated fertilizers in Zea mays cultivation in an acid soil. Liquid organic-N fertilizers with different sources of humic molecules were evaluated. The treatments were applied at 10 and 20 days after sowing (DAS) of corn. Plant and soil samples were collected at 54 DAS (tasseling stage) and analyzed for N, P, K, Ca, Mg and Na. The use of liquid organic-N fertilizer increased N content in leaf, stem and roots. The fertilizer with Fulvic acids (FA) increased N uptake and use efficiency. It also improved exchangeable Ca and Mg in soil solution. No significant difference was observered for soil exchangeable K. It can be concluded that the use of organic substances could enhance N uptake and N use efficiency of corn.